2004
DOI: 10.1111/j.1399-0039.2004.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I and class II genotyping in patients with Behcet's disease: a regional study of eastern part of Turkey

Abstract: Class I human leucocyte antigen (HLA)-B51 is well known to be associated with Behcet's disease in many ethnic groups. However, there has been no published paper with respect to its association with HLA class I and class II among the Turkish people who live in the eastern region of Turkey. Moreover, as it is known that B51 antigen is encoded by 21 alleles, B*5101-5121, HLA-B51 allele typing was performed, as well as HLA class I and class II genotyping of 75 patients with the disease and the 54 individuals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 11 publications
(16 reference statements)
5
48
2
Order By: Relevance
“…24 According to two small non-population based studies, -one from the West and the other from the East of Turkey-the frequency of HLA-B27 varies between 2.8% and 11.1% in Turkey. 25,26 This considerably broad range of HLA-B27 frequency suggests an apparent interregional variation in the prevalence of SpA. However, we are not sure whether the heterogeneity of regional prevalence of SpA in Turkey can be explained by HLA-B27 frequency, as no nationwide data exist on the prevalence of HLA-B27.…”
Section: Discussionmentioning
confidence: 99%
“…24 According to two small non-population based studies, -one from the West and the other from the East of Turkey-the frequency of HLA-B27 varies between 2.8% and 11.1% in Turkey. 25,26 This considerably broad range of HLA-B27 frequency suggests an apparent interregional variation in the prevalence of SpA. However, we are not sure whether the heterogeneity of regional prevalence of SpA in Turkey can be explained by HLA-B27 frequency, as no nationwide data exist on the prevalence of HLA-B27.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Both HLA-B5101 and -B5102 were detected in patients with ocular involvement in ABD. [26][27][28] Also, MICA006 (MHC class I chain related gene A) gene, which lies directly beside the HLA-B51 gene on chromosome 6, was found in ABD patients. 29,30 It is unknown whether the gene product has a pathological effect or it enables an autoimmune reaction triggered by a pathogen similar to HLA-B, so that it is not detected and eliminated by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, genetic dispersion is very different between geographical regions.In our country, some studies were reported about HLA distribution in Mediterranean, Thracian, Eastern and Central Anatolia regions of Turkey. [11][12][13][14] Also there is a study about HLA dispersion of overall Turkey. [15] But there is no study about Blacksea region.…”
Section: Discussionmentioning
confidence: 99%